Was the economic crisis 1997–1998 responsible for rising suicide rates in East/Southeast Asia? A time–trend analysis for Japan, Hong Kong, South Korea, Taiwan, Singapore and Thailand - Chang, Shu-Sen; Gunnell, David; Sterne, Jonathan A.C.; Lu, Tsung-Hsueh; Cheng, Andrew T.A. (Social science & medicine (1982), 2009)
In 1997–1998 a widespread economic crisis hit the economies of many East/Southeast Asian countries; its impact on suicide rates across the region has not been systematically documented. We investigated the impact of the Asian economic crisis (1997–1998) on suicide in Japan, Hong Kong, South Korea, Taiwan, Singapore and Thailand. Suicide and population data for the period 1985–2006 were extracted from the World Health Organisation's mortality database and Taiwanese mortality statistics. Sex-specific age-standardised suicide rates for people aged 15 years or above were analysed using joinpoint regression. Trends in divorce, marriage, unemployment, gross domestic product (GDP) per capita and alcohol consumption were compared with trends in suicide rates graphically and using time-series analysis. Suicide mortality decreased in the late 1980s and early 1990s but subsequently increased markedly in all countries except Singapore, which had steadily declining suicide rates throughout the study period. Compared to 1997, male rates in 1998 rose by 39% in Japan, 44% in Hong Kong and 45% in Korea; rises in female rates were less marked. Male rates also rose in Thailand, but accurate data were incomplete. The economic crisis was associated with 10,400 more suicides in 1998 compared to 1997 in Japan, Hong Kong and Korea. Similar increases in suicide rates were not seen in Taiwan and Singapore, the two countries where the economic crisis had a smaller impact on GDP and unemployment. Time-series analyses indicated that some of the crisis's impact on male suicides was attributable to increases in unemployment. These findings suggest an association of the Asian economic crisis with a sharp increase in suicide mortality in some, but not all, East/Southeast Asian countries, and that these increases were most closely associated with rises in unemployment.